1996
DOI: 10.1002/jts.2490090217
|View full text |Cite
|
Sign up to set email alerts
|

Childhood factors and war zone stress in chronic PTSD

Abstract: This study assessed the predictive validity of combat factors and selected premilitary variables (i.e., childhood physical abuse, substance abuse in the family of origin, or being raised in a nonadaptive or noncohesive family) on posttraumatic stress disorder (PTSD) group membership. In addition, it assessed the correlation of combat exposure and selected premilitary variables with the severity of PTSD symptomology. Ninety-three male Vietnam combat veterans with PTSD were compared to 82 male Vietnam combat vet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Karl’s case was conceptualized from a cognitive-behavioral perspective. The interaction of potential genetic risk factors (Broekman, Olff, & Boer, 2007) and early childhood abuse (Donovan, Padin-Rivera, Dowd, & Blake, 1996) likely predisposed the development of PTSD. During deployment to Somalia, he witnessed severe human suffering.…”
Section: Case Conceptualizationmentioning
confidence: 99%
“…Karl’s case was conceptualized from a cognitive-behavioral perspective. The interaction of potential genetic risk factors (Broekman, Olff, & Boer, 2007) and early childhood abuse (Donovan, Padin-Rivera, Dowd, & Blake, 1996) likely predisposed the development of PTSD. During deployment to Somalia, he witnessed severe human suffering.…”
Section: Case Conceptualizationmentioning
confidence: 99%
“…Several studies (e.g., Andrews, Brewin, Rose, & Kirk, 2000; Bremner, Southwick, Johnson, Yehuda, & Charney, 1993; Donovan, Padlin-Rivera, Dowd, & Blake, 1996) and a recent meta-analysis (Brewin et al, 2000) have shown that a history of childhood physical abuse is a significant risk factor for the development of PTSD after a subsequent exposure to a trauma. However, little research has documented whether the level of violence in a society and in its child rearing practices has any societal-level influence on rates of PTS symptoms in victims of a given traumatic event, such as sustaining IPV.…”
Section: An International Perspectivementioning
confidence: 99%
“…First, the literature has focused primarily on 1 or 2 types of events (usually childhood sexual abuse and physical abuse) in a particular study. 7,[10][11][12] There are only a few studies that have examined the impact of other traumas such as accidents, natural disasters, or personal illness. 13 Second, most studies examining the effects of childhood abuse on PTSD symptoms have relied on trauma measures that have not been standardized or normed on the general population and thus may not be especially helpful in clinical contexts.…”
mentioning
confidence: 99%